2004
DOI: 10.1002/cbdv.200490079
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Odoriferous Sulfanylalkanols in Human Axilla Secretions and Their Formation through Cleavage of Cysteine Precursors by a CS Lyase Isolated from Axilla bacteria

Abstract: Human axillary odor is known to be formed upon the action of Corynebacteria sp. on per se odorless axilla secretions. Besides the known odoriferous acids, we report the occurrence in human axilla secretions of four odoriferous sulfanylalkanols, namely 3-sulfanylhexan-1-ol (3), 2-methyl-3-sulfanylbutan-1-ol (4), 3-sulfanylpentan-1-ol (5), and 3-methyl-3-sulfanylhexan-1-ol (6). These compounds have a pungent sweat/kitchen odor, also reminiscent of onions with some fruity connotations, and perception thresholds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(139 citation statements)
references
References 27 publications
7
127
0
Order By: Relevance
“…As observed previously (Shelley et al 1953;Troccaz et al 2004;Natsch et al 2006), both the concentrated hexane fraction and the concentrated aqueous fraction of sweat samples obtained by physical exercise had only a faint odour, which is in line with the well-established notion that odour is only released by bacterial action (Shelley et al 1953). Within a pooled hexane fraction, a large number of components were identified by routine database comparison, but the 25 most abundant peaks appear either to be exogenous (especially fragrance components, emollients used in cosmetics, plasticizers and antioxidants) or they are simple fatty acids (C14-C18, saturated and unsaturated) and squalene, compounds generally present in the skin.…”
Section: Identification and Selection Of Target Analytes In The Odorasupporting
confidence: 80%
See 4 more Smart Citations
“…As observed previously (Shelley et al 1953;Troccaz et al 2004;Natsch et al 2006), both the concentrated hexane fraction and the concentrated aqueous fraction of sweat samples obtained by physical exercise had only a faint odour, which is in line with the well-established notion that odour is only released by bacterial action (Shelley et al 1953). Within a pooled hexane fraction, a large number of components were identified by routine database comparison, but the 25 most abundant peaks appear either to be exogenous (especially fragrance components, emollients used in cosmetics, plasticizers and antioxidants) or they are simple fatty acids (C14-C18, saturated and unsaturated) and squalene, compounds generally present in the skin.…”
Section: Identification and Selection Of Target Analytes In The Odorasupporting
confidence: 80%
“…We had shown that most of these acids are odorants and that they occur in different ratios on different individuals, but whether these ratios are stable over time and whether they are genetically fixed had not been investigated. Finally, different sulfanylalkanols have been reported by several authors as further odour components in axilla secretions (Hasegawa et al 2004;Natsch et al 2004;Troccaz et al 2004). Interestingly, these specific human body odorants were not detected at all in the analytical population studies summarized above addressing the question of an individual-specific odour type (Curran et al 2005;Penn et al 2007).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations